Pengaruh Bakat dan Informasi Karir Terhadap Pemilihan Karir Siswa Kelas XII SMA Negeri 10 Sarolangun: Perspektif Teori Perkembangan Karir Donald Super - Miftahul Rahmah; Dina Hajja Ristianti; Fadila Fadila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Talent and career information are two factors that may influence students’ career choices. This study aimed to describe the level of career choice and analyze the partial and simultaneous effects of talent and career information on the career choices of Grade XII students at SMA Negeri 10 Sarolangun. A quantitative correlational design with multiple linear regression analysis was employed. The population consisted of 40 students, with 37 students selected through purposive sampling and the Slovin formula at a 5% margin of error. Data were collected using Likert-scale questionnaires measuring talent, career information, and career choice, supported by documentation. The instruments were tested for validity and reliability. Data analysis included descriptive statistics, normality, linearity, multicollinearity, Pearson correlation, and multiple linear regression tests. The mean scores for talent, career information, and career choice were 218.89, 217.03, and 217.84, respectively, indicating relatively high levels. Talent had a strong correlation with career choice (r=0.709; p<0.05) and a significant positive regression coefficient of 0.475. Career information had a very strong correlation with career choice (r=0.825; p<0.05). Simultaneously, both variables significantly influenced career choice. These findings support Donald Super’s career development theory regarding the relationship among self-concept, career exploration, and the information environment.